Dangerous prey and daring predators: a review - Mukherjee, Shomen; Heithaus, Michael R. (Biological reviews of the Cambridge Philosophical Society, 2013)
ABSTRACT How foragers balance risks during foraging is a central focus of optimal foraging studies. While diverse theoretical and empirical work has revealed how foragers should and do manage food and safety from predators, little attention has been given to the risks posed by dangerous prey. This is a potentially important oversight because risk of injury can give rise to foraging costs similar to those arising from the risk of predation, and with similar consequences. Here, we synthesize the literature on how foragers manage risks associated with dangerous prey and adapt previous theory to make the first steps towards a framework for future studies. Though rarely documented, it appears that in some systems predators are frequently injured while hunting and risk of injury can be an important foraging cost. Fitness costs of foraging injuries, which can be fatal, likely vary widely but have rarely been studied and should be the subject of future research. Like other types of risk‐taking behaviour, it appears that there is individual variation in the willingness to take risks, which can be driven by social factors, experience and foraging abilities, or differences in body condition. Because of ongoing modifications to natural communities, including changes in prey availability and relative abundance as well as the introduction of potentially dangerous prey to numerous ecosystems, understanding the prevalence and consequences of hunting dangerous prey should be a priority for behavioural ecologists.